2019
DOI: 10.1007/s11248-019-00168-9
|View full text |Cite
|
Sign up to set email alerts
|

Introducing gene deletions by mouse zygote electroporation of Cas12a/Cpf1

Abstract: CRISPR-associated (Cas) nucleases are established tools for engineering of animal genomes. These programmable RNA-guided nucleases have been introduced into zygotes using expression vectors, mRNA, or directly as ribonucleoprotein (RNP) complexes by different delivery methods. Whereas microinjection techniques are well established, more recently developed electroporation methods simplify RNP delivery but can provide less consistent efficiency. Previously, we have designed Cas12a-crRNA pairs to introduce large g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…We recently developed a new method, named TAKE, that could produce genome-edited animals by electroporation instead of the microinjection method [ 5 , 6 , 7 ]. Many kinds of knockout and knock-in mice and rats have already been produced by TAKE method using ZFN, TALEN, CRISPR-Cas system [ 12 , 13 , 14 , 15 , 16 , 17 ], and other nucleases [ 18 ]. Furthermore, this method has widely been applied for the production of genome-edited strains in other animals [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recently developed a new method, named TAKE, that could produce genome-edited animals by electroporation instead of the microinjection method [ 5 , 6 , 7 ]. Many kinds of knockout and knock-in mice and rats have already been produced by TAKE method using ZFN, TALEN, CRISPR-Cas system [ 12 , 13 , 14 , 15 , 16 , 17 ], and other nucleases [ 18 ]. Furthermore, this method has widely been applied for the production of genome-edited strains in other animals [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study published in 2019 utilized Cas12a instead of Cas9 as the nuclease, and targeted three different genes with electroporation. The authors found knockout mutation rates in mouse embryos ranged from 34 to 70% (Dumeau et al, 2019). Unfortunately, mosaicism rates were not studied.…”
Section: Electroporation-mediated Knockoutsmentioning
confidence: 99%
“…Of the challenges and approaches of delivering CRISPR, it was pointed out [ 18 , 51 ] that although the present genome engineering is in favor of CRISPR tools, TALENs may still be of a primary choice in certain experimental species. For example, TALENs have been utilized in targeted genomic editing in Xenopus tropicalis by knocking-out Klf4 [ 49 , 50 ] or thyroid hormone receptor α [ 23 ].…”
Section: Gene Deliverymentioning
confidence: 99%
“…To deliver the carrying DNA sequence to target cells, non-viral techniques such as electroporation, lipofection, and microinjection can also be used [ 18 ]. In addition, these techniques also reduce off-target cleavages problems.…”
Section: Gene Deliverymentioning
confidence: 99%